Engagement opportunities in OECD NEA benchmark development - Bess, John D.; Blaise, Patrick; Buss, Oliver; DeHart, Mark; Fleming, Michael; Hill, Ian; Ilas, Germina; Ivanova, Tatiana; Ivanov, Evgeny; Marshall, William J.; Martin, Julie-Fiona; Miller, Thomas; et al. (Frontiers in Energy Research, 2023)
A myriad of opportunities is available to collaborate via international benchmark exercises and experimental data preservation activities. Many such opportunities abound under the auspices of the Nuclear Science Committee of the Organisation for Economic Co-operation and Development Nuclear Energy Agency (NEA). Key projects and activities of relevance to the development of advanced reactors design include the International Criticality Safety Benchmark Evaluation Project (ICSBEP), the International Reactor Physics Experiment Evaluation Project (IRPhEP), the International Assay Data of Spent Nuclear Fuel Database (SFCOMPO), the Shielding Integral Benchmark and Archive Database (SINBAD), and The International Experimental Thermal HYdraulicS Database (TIETHYS), and various cooperative benchmark exercises. Interested participants are encouraged to contact the leadership and secretariat of the various Technical Working Groups and Working Parties to become more engaged. This paper provides a summary of the current benchmark exercises and experimental databases available for international participation.